Multi-level determinants of tuberculosis treatment completion in rural Uganda: A cross-sectional study - Munanura Turyasiima; Daniel Muliika; Gaston Turinawe; Miriam Acheng; Antony Ikiriza; Agnes Alinde; Precious Natureeba; Amon Nkwansiibwe; Balbina Gillian Akot; Susan Wendy Wandera Kayizzi; Derrick Asaasira; Shamim Nantege; et al. (PLoS ONE, 2026)
Background Tuberculosis (TB) treatment completion rates in high-burden countries like Uganda often fall short of the WHO End TB Strategy target of ≥90%. This study evaluated multilevel determinants of treatment completion to guide evidence-based improvement strategies in rural Western Uganda. Methods We conducted a cross-sectional, multi-center analytical study of 224 patients with drug-susceptible TB across four public health facilities in Kakumiro District. Eligible participants had been on treatment for at least six months. Data collected via structured questionnaires were validated against facility TB registers. Multivariable logistic regression identified independent predictors, reported as adjusted odds ratios (AOR) with 95% confidence intervals (CI). Results The treatment completion rate was 82.6% (185/224), with a 30.4% TB-HIV co-infection rate. Significant positive predictors included high TB knowledge (AOR = 14.0; 95% CI: 3.06–24.5), high economic status (AOR = 7.2; 95% CI: 1.63–31.5), belief in treatment efficacy (AOR = 6.2; 95% CI: 2.02–18.8), and respectful health worker behavior (AOR = 5.0; 95% CI: 2.15–11.83). Community-level support was critical, specifically religious/community leader advocacy (AOR = 4.2; 95% CI: 1.84–9.51) and community health worker (CHW) home visits (AOR = 3.5; 95% CI: 1.64–7.72). Waiting time less than 30 minutes (AOR = 6.3, 95% CI: 1.91–20.96) also positively impacted TB treatment completion. Major negative predictors were male gender (AOR = 0.3; 95% CI: 0.11–0.86), drug stockouts (AOR = 0.3; 95% CI: 0.11–0.70), belief in traditional cures (AOR = 0.3; 95% CI: 0.13–0.71), and stigma (AOR = 0.4; 95% CI: 0.16–0.80). Conclusion Achieving the WH O End TB targets requires integrated, multilevel interventions. Efforts should focus on male-targeted engagement, strengthening supply chains to eliminate drug stockouts, enhancing CHW-led community outreach, and reducing stigma to ensure equitable treatment success.